Milk matters 4.0: bridging milk donor, staff and student needs towards a purposeful and maintainable system - Talbot, Deborah (Department of Computer Science, 2025)
Milk Matters is a Cape Town based non-profit milk bank. Their primary role is to collect expressed breastmilk from donor mothers, pasteurize it and distribute it to recipient infants in need. This dissertation explores the design and deployment of a donor-facing mobile application and staff-facing web application developed with and for the non-profit organisation (NPO) over the course of postgraduate student projects from 2016 to 2023. A particular focus is on the effects that the communication and feedback provided by the application has on donors' motivation to donate breastmilk. The staff-facing web application allows staff to manage the dynamic content of the mobile application. Additionally, we ask questions about the challenges associated with university-NPO collaborations on mobile development and reflect on design for this context. Technical and procedural challenges faced when getting the mobile application into a deployable state were noted. A pilot study was performed with three donors, followed by a deployment evaluation phase with seven donors and two NPO staff. Qualitative evaluation was done through semi-structured interviews and quantitative data was collected through usage analytics. The mobile application has shown the ability to increase donors' motivation to donate through increased communication between the NPO and its donors and result in donors feeling more appreciated. This occurred through direct communication from within the Donor App, automatic in-app feedback and passive app content. The extent to which donors engage with the mobile application and benefit from it, depends on their personal reasoning for becoming a donor. Donors' usage of the application also results in operational benefits for the milk bank. Challenges encountered in the deployment and maintenance of university-led mobile application development for this low-resourced NPO, highlight the effort required to sustain mobile applications in the app stores. To reduce barriers to future project continuity, recommendations include a clear handover of access to all project related accounts to the project supervisor, secure online access to all project related information and planning for continued contact with outgoing students.